Assessments of key features and Taguchi analysis on hydrogen rich syngas production via gasification of polyethylene, polypropylene, polycarbonate and polyethylene terephthalate wastes. (23rd August 2021) - Mojaver, Mehran; Azdast, Taher; Hasanzadeh, Rezgar
Abstract: Plastics have a considerable contribution on volumetric portion of the worldwide municipal solid waste. Gasification of plastic waste is an efficient thermo-chemical approach with a bright outlook. In the present study, the steam gasification of polyethylene, polypropylene, polycarbonate and polyethylene terephthalate waste was modeled. The effects of key features including steam to plastic waste ratio, temperature, moisture content, and pressure were assessed on hydrogen-rich syngas compositions and exergy destruction rate. Taguchi approach was utilized to investigate and optimize the process. The findings revealed that the gasification of polypropylene waste led to the highest hydrogen production at all processing conditions. However, the lowest exergy destruction rates belonged to polyethylene waste gasification. The results of analysis of variance showed that steam to plastic waste ratio had the highest contributions on hydrogen production and exergy destruction rate with 53.13% and 59.53%, respectively. Signal to noise ratio analysis was hired to multi-objective optimize the plastic waste gasification. Polyethylene waste, 1.75 of steam to plastic waste ratio, 1300 K of temperature, 10% of moisture, and 400 kPa of pressure were the optimum conditions. Hydrogen production was 66.71% and exergy destruction rate was 54.86 kW at the optimum conditions. Highlights: Hydrogen rich syngas of plastic waste gasification was studied versus key features. Gasification of PE, PP, PC and PET wastes was conducted. Taguchi approach was utilized to optimize the plastic waste gasification process. Multi-objective optimization was performed for hydrogen and exergy destruction. Optimum hydrogen production was 66.71% and exergy destruction rate was 54.86 kW.